Hybrid CaO/ZnFe2O4 Modified with Al2O3 as a Green Catalyst for Biodiesel Production from Waste Cooking Oil - Hapsari, Jenia Villa; Helmiyati, Helmiyati; Krisnandi, Yuni K. (Department of Chemistry, Faculty of Science and Technology Syarif Hidayatullah Jakarta State Islamic University, 2024)
In this work, biodiesel was produced from waste cooking oil (WCO) via a green catalyst of CaO-ZnFe2O4 modified Al2O3. The catalyst was characterized using Fourier-transform infrared spectroscopy (FTIR), X-ray powder diffraction (XRD), scanning electron microscopy (SEM), energy dispersive x-ray (EDX), SEM-mapping, Brunauer-Emmett-Teller (BET), transmission electron microscopy (TEM) analyses. The catalyst performance was studied in the transesterification reaction of WCO conversion to biodiesel. The catalytic activity increased with the combination of nanoparticles effect and support catalysts obtained biodiesel yield of nano-Al2O3, nano-CaO, ZnFe2O4, CaO-ZnFe2O4, and CaO-ZnFe2O4/Al2O3 is 36.86%, 67.16%, 74.83%, 86.54%, and 93.41%, respectively. The best biodiesel yield was 93.41% with a mass ratio of Al2O3 to CaO-ZnFe2O4 (2:1). The physicochemical properties (acid number, density, kinematic viscosity, flash point, and cetane number) of biodiesel under the optimal conditions agreed with the ASTM standard. These results show that the developed nanocomposite has great potential to reduce biodiesel production costs because derived from WCO. In conclusion, CaO-ZnFe2O4 modified Al2O3 as a catalyst has a high potential for biodiesel production on a large scale.